Fracture behaviors of ceramic tissue scaffolds for load bearing applications - Entezari, Ali (Sci Rep, 2016)
Healing large bone defects, especially in weight-bearing locations, remains a challenge using available synthetic ceramic scaffolds. Manufactured as a scaffold using 3D printing technology, Sr-HT-Gahnite at high porosity (66%) had demonstrated significantly improved compressive strength (53 ± 9 MPa) and toughness. Nevertheless, the main concern of ceramic scaffolds in general remains to be their inherent brittleness and low fracture strength in load bearing applications. Therefore, it is crucial to establish a robust numerical framework for predicting fracture strengths of such scaffolds. Since crack initiation and propagation plays a critical role on the fracture strength of ceramic structures, we employed extended finite element method (XFEM) to predict fracture behaviors of Sr-HT-Gahnite scaffolds. The correlation between experimental and numerical results proved the superiority of XFEM for quantifying fracture strength of scaffolds over conventional FEM. In addition to computer aided design (CAD) based modeling analyses, XFEM was conducted on micro-computed tomography (μCT) based models for fabricated scaffolds, which took into account the geometric variations induced by the fabrication process. Fracture strengths and crack paths predicted by the μCT-based XFEM analyses correlated well with relevant experimental results. The study provided an effective means for the prediction of fracture strength of porous ceramic structures, thereby facilitating design optimization of scaffolds.